(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article is devoted to the important characteristics of the lingua-cultural components of the English language. The lingua-cultural knowledge can be got by students through original texts that contain plenty of lingua-cultural units. It highlights the peculiar usage of lingua-cultural units in everyday life. The reader can analyze the given examples of lingua-cultural units and think over their future possible usage in his speech. Conclusions are based on the results of the conducted linguistic experiments.